ANALISIS ANGGARAN RESPONSIF GENDER DI KABUPATEN KENDAL TAHUN ANGGARAN 2017– 2018 - Diny Ayu Wulandhari; Puji - Astuti (Journal of Politic and Government Studies, 2022)
Gender Responsive Budgeting was an integration of PUG that can accommodate justice for women and men to have equal opportunities in obtaining access, benefits, participation, and equality in development achievements. However, the reality on the ground, especially in Kendal Regency, is that the implementation of gender-responsive budgeting is still not optimal in accommodating gender needs. This is suspected because gender issues have not become a priority issue and SKPD still does not understand what is meant by ARG.This study aims to find out how the implementation and constraints that affect the implementation of the gender-responsive budget in Kendal Regency 2017-2018 fiscal year. The method in study is descriptive qualitative research with data collection techniques through interviews and documentation. In which case, the author will research and interview several informants at SKPD who have implemented ARG in detail in the hope of obtaining comprehensive data related to ARG.The results of this study show that the implementation of ARG in Kendal Regency is still not optimal and there are no points that require SKPD to budget for gender responsiveness. Of the 33 SKPDs, there are only 6 SKPDs that carry out ARG. The analysis of the budget allocation category, Special Budget for Gender Targets, there are 21 programs, the Gender Equality Institutional Budget has 5 programs and the Gender Equality Budget in General there are 22 programs. Constraints on the implementation of gender-responsive budgets are policy factors including legal strength and government commitment, structural factors including human resource capacity and the dominance of structures and cultural factors including the degree of women's participation and gender views.The suggestion that can be conveyed to the Kendal Regency Regional Government is that the Kendal Regency Regional Government can formulate regional policies through regional regulations as a clear implementation guideline in regulating PUG and ARG, so that all SKPD or regional autonomy implementing bodies will overall compile programs and activities that respond to gender needs. So that the implementation of ARG in the Kendal Regency Regional Government can run optimally